THE IMPORTANCE OF GREEN ACCOUNTING IN THE BANKING SECTOR IN UZBEKISTAN: ANALYSIS OF DIFFERENCES IN PERCEPTIONS BETWEEN ACADEMICS AND PROFESSIONALS - Ugli, Odiljonov Makhmudjon Murodjon; R Nelly Nur Apandi; Arim Nasim (Journal of Innovation Research and Knowledge, 2025)
This study investigates the differences in perceptions between academics and banking professionals regarding the importance of green accounting in the banking sector of Uzbekistan. With a growing global emphasis on sustainability and environmental responsibility, green accounting has emerged as a critical tool for integrating ecological concerns into financial decision-making. Despite its relevance, its adoption in Uzbekistan remains limited. Data were collected from 20 academics and 20 banking professionals using a quantitative survey method. Descriptive statistics and an independent samples t-test were used to analyze perception differences. The results indicate that perceive professionals about green accounting as significantly more important than academics This gap reflects differing awareness, exposure, and priorities related to environmental accounting practices. The findings underscore the need for increased collaboration between academia and industry and policy interventions to enhance the understanding and implementation of green accounting in the Uzbek banking sector.